Factors Affecting COVID-19 Budget Refocusing: Based on the Agenda Setting – Punctuated Equilibrium Theory - Rachmadani, Wulan Suci; Suhardjanto, Djoko; Almasyhari, Abdul Kharis; Widarjo, Wahyu; Rosadi, Samsul (European Journal of Applied Sciences, 2022)
The COVID-19 pandemic has had a major impact on changes in the social and economic conditions of people in Indonesia. The implementation of the budget refocusing policy is one of the strategies in overcoming the impact of COVID-19 on the national economy. This study examines the factors that influence the budget refocusing policy in Indonesia. The population in this study is local governments throughout Indonesia which consist of 415 regencies. This study uses a judgment sampling technique. The research data were analyzed using multiple regression analysis with the control variable in the form of Budget Evaluation. The results showed that these Variables of Number of Surges in COVID-19 Cases, Economic Growth, Realization of Capital Expenditures, and Control Variable of Budget Evaluation had a significant effect on Refocusing Regional Government Budgets, while the Unemployment Rate Variable had no effect on Regional Government Budgets Refocusing. This study contributes to the addition of literature related to Regional Government Budgets Refocusing as a step to deal with COVID-19 in the economic and social fields.